Penerapan Pompa Air Tenaga Surya Untuk Sarana Irigasi dan Edukasi Desa Wisata Widarapayung Wetan Cilacap - Supriyono, Supriyono; Riyanto, Sugeng Dwi; Yusuf, Muhamad; Purwiyanto, Purwiyanto; Prasetya, Vicky; Prihantara, Andesita (Politeknik Negeri Cilacap, 2024)
Widarapayung Wetan Village was designated as an innovation village by the Cilacap Regency Innovation Village Determination which is located in Binangun District, Cilacap Regency. The main potential of Widarapayung Wetan Village is in the tourism sector, such as Widarapayung Beach and the pioneering tourist village. The facilities that have been built and already exist in this pilot tourism village are an art performance stage, pavilion, gazebo, gamelan instruments, plantation land, and rice fields. One of the pioneering developments of tourist villages is the development of educational tourism. This community service activity applies appropriate technology by developing water pump technology for irrigating rice fields using solar energy. Apart from irrigating rice fields, this solar-powered water pump technology is also used for educational tourism at the Widarapayung Wetan tourism village pilot, especially in the field of utilizing new and renewable energy. The stages of work carried out included surveying the installation site, designing and manufacturing a solar water pump system, system installation at the installation site, operational trials of pumps, and operational training and pump maintenance. The result of this activity is a solar water pump system for irrigating rice fields with a capacity of 30 liters/minute.